Hurler disease (mucopolysaccharidosis type IH): clinical features and consanguinity in Tunisian population - Chkioua Latifa; Khedhiri Souhir; Ben Turkia Hadhami; Chahed Henda; Ferchichi Salima; Ben Dridi Marie; Laradi Sandrine; Miled Abdelhedi (BMC, 2011)
Abstract Mucopolysaccharidosis type I (MPS I) was a group of rare autosomal recessive disorder caused by the deficiency of the lysosomal enzyme, alpha -L -iduronidase, and the resulting accumulation of undergraded dematan sulfate and heparan sulfate. MPS I patients have a wide range of clinical presentations, that makes it difficult to predict patient phenotype which is needed for genetic counseling and also impedes the selection and evaluation of patients undergoing therapy bone marrow transplantation. Aim of the study consanguinity rates have been determined among 14 families with mucopolysaccharidosis type I, seen in the pediatric departments of different geographic areas of Tunisia (Central and Southern areas) for the period August 2004 - August 2011 in order to investigate the relation between consanguinity and this disorder. Patients and methods Clinical and molecular analyses confirmed the diagnosis for MPS type I in the studied families. Results Most of the Tunisian MPS I patients have been identified at the homozygous status: p.P533R mutation (7 homozygous and one double heterozygous p.L578Q/p.P533R patients; 41.66% of all the investigated MPSI patients), p.F177S (1 homozygous patient; 5.55%), p.L530fs (1 patient; 5.55%), p.Y581X (2 patients; 11.11%), p.F602X (3 patients; 16.66%), p.R628X (1 patient; 5.55%). Another mutation: p.L578Q has been identified at the heterozygous status in the only double heterozygous p.L578Q/p.P533R case. Part of the mutations was the result of a founder effect. These described points are the consequences of the high rate of consanguinity. Conclusion The high frequency of p.P533R mutation could be explained by the high degree of inbreeding. This is due to the richness of the genetic background of the studied population. A multidisciplinary approach is essential to develop adequate preventive program adapted to the social, cultural, and economic context.